Pope Sixtus IV at Santa Maria del Popolo: Marian Devotion and the Papal Agenda - Kuziow, Shannon E. (The sixteenth century journal, 2024)
Throughout much of his career in the Catholic Church, Pope Sixtus IV was actively involved in promoting the cult of the Virgin Mary. He directly sponsored the construction or renovation of several Marian sites in Rome, including the Church of Santa Maria del Popolo, which houses a miraculous icon of the Madonna. Inside the church, Sixtus performed weekly devotions and regularly held ceremonies bolstering and celebrating the major political events of his pontificate. Through an analysis of the papal rituals that unfolded before the icon, this article demonstrates that Sixtus's dedication to the Madonna served as a vehicle of expression for advancing the interconnected theological, devotional, and political aspects of his papal agenda. It further argues that the pope's support of the Marian cult played a crucial role in his perceived ability to harness divine aid in the larger temporal issues plaguing the universal Church.